THE EFFECT OF PROBLEM BASED LEARNING MODEL ON THE ABILITY TO THINK CREATIVELY MATHEMATICALLY OF STUDENTS OF SMK KESEHATAN BENGKALIS - Hafiza, Hafiza Widia Sari; Aulia Sthephani (Mathematics Research and Education Journal, 2024)
This study aims to determine the effect of the Problem Based Learning model on the mathematical creative thinking ability of students of SMK Kesehatan Bengkalis. This research is a quasi experimental research (Quasi Experiment) with a research design of Nonequivalent Control Group Design. The population in this study were all students of class X SMK Kesehatan in the 2023/2024 academic year. The sample of this research is class X pharmacy A as the control class and class X pharmacy B as the experimental class, with a total of 19 control class students and 20 experimental class students. The data collection instrument in this study was the Pretest and Posttest sheets. The data collection technique was carried out with a test technique. The data analysis technique used is descriptive analysis and inferential analysis. So it can be concluded that there is an effect of the Problem Based Learning model on the creative thinking ability of students.